Integration/Interaction of oncologic growth - Meadows, Gary G. (Cancer growth and progression, 2005)
The present multi-volume Book Series, CANCER GROWTH AND PROGRESSION, encompasses the widest possible framework of cutting edge research in the field of neoplastic pathology and other integrated fields. Normal and pathologic growth is one of the most intensively studied yet challenging areas in pathology. Thus the individual volumes in this series focus on the topics of highest scientific interest for basic and clinical researchers, pathologists, medical and surgical oncologists and allied multidisciplinary teams interested in the study of these aspects of neoplastic growth, progression and inhibition. The range of topics covered is extensive, including but not limited to autonomous growth characteristics of malignancy, phenomena of progression of malignant growth involving the various body systems, and recent advances being made in successful neoplastic inhibition and control. Cell function may be described as producing progression or regression, often found as alternating features in tumors or as variations between normal tissues and tumors. The source of regression in normal melanin producing cells may not be the same as in melanomas. These functions of living matter persist in all phyla of eumetazoans vascular plants as well as in particular species of fungi. However, homo sapiens are the eumetazoan species, which interest us the most. Normal growth processes cannot be entirely understood in all its diversity until we have a thorough knowledge of what constitutes normal growth in various organisms. Microenvironmental effects on tumour progression and metastasis -- Role of microenvironment on gene expression, angiogenesis and microvascular function in tumors -- Imaging of angiogenesis in vivo with fluorescent proteins -- The epigenetic influence of the tumor microenvironment on melanoma plasticity -- Dynamics of cell adhesion interactions during melanoma development -- Matrix metalloproteinases: mediators of tumour-host cell interactions -- Role of brain microenvironment in brain metastases -- Influence of the bone microenvironment on breast cancer metastasis to bone -- Interaction of tumour with host stroma in hepatocellular carcinoma -- Dynamic nature of tumour-host interactions within the tumor microenvironment -- rreast cancer progression: A “Vicious Cycle” of pro-malignancy activities is mediated by inflammatory cells, chemokines and cytokines -- Tumor and host endothelial cell selective interactions and modulation by microenvironmental chemokines: tumor-endothelial cell cross talk specificity -- The role of chemokine receptors, in particular CXCR4, in lymphoma and carcinoma metastasis -- Energy homeostasis and the tumor/host interaction: The role of the brain -- Anti-angiogenic and pro-apoptotic effects of dietary restriction in experimental brain cancer: role of glucose and ketone bodies -- Dietary restriction of specific amino acids modulates tumor and host interactions -- Role of tumour microenvironment in chemoresistance -- Integrin-mediated resistance to chemotherapy-induced apoptosis in cancer cells -- Bone metastasis microenvironment participates in the development of androgen ablation refractoriness and chemotherapy resistance of prostate cancer cells residing in the skeleton: clinical implications -- Current and future therapeutic targets of the tumour-host microenvironment -- Bone stromal cells as therapeutic targets in osseous metastasis -- Organotropism of lung lung cance ...